Obtención del factor de planta mediante evaluación del potencial de energía eólica y solar proporcionada por una central hibrida ubicada en el cantón Latacunga provincia de Cotopaxi. - Chicaisa Ugsha, Jairo Marcelo (2020)
This research project aimed to get and analyze the net capacity factor of the hybrid generation system that has been installed in Latacunga, belonging to M&V Engineers Enterprise. The system developed makes use of the sun and wind, renewable resources. Therefore, to reach the get objective, a history data from a meteorological station were processed to acquire solar irradiation and wind speed at the point of the study. The dataset attained for 3 months since the net capacity factor has been by data of at least one year with a database called Renewables.ninja, which allows running simulations of hourly power output from wind and solar power plants in any location the world. The data obtained by meteorological station measurements were installed in the course of procedure to bring the wind and solar potential, and these were compared with values of the database mentioned above to determine the deflection. Once the data has been validated, the hybrid generation system's net capacity factor was obtained, which is 18.79%. This work permitted to determine the available potential in the established zone, which will allow the enterprise to have the necessary criterion to assess the capacity of new systems to be implemented according to the possibility of available renewable resources and thus avoid an oversizing, and this yields savings in time and money.